The Effect of Helsinki Agreements to the Issue of Freedom for Lithuania - Banionis, Juozas (Genocidas ir rezistencija, 1999)
When the West was promoting greater international co–operation with the East, the 1970s set the stage not only in Europe but also worldwide for a shift away from the ‘Cold War’ policy towards the ‘peaceful co–existence’ declared by the Soviets. The favourable international situation allowed the USSR to focus more on overcoming loads of domestic economic difficulties and reducing its investment in the East–West military rivalry. This international situation rightly made the Lithuanian diaspora in the West – to be more precise, free Lithuania – worry about the fate of Lithuania’s decades–old freedom cause. In other words, with the threat of weakening support for the Baltic freedom struggle, it became relevant to investigate whether the official US position on the illegal incorporation of the Baltic states into the USSR was changing, and to try to influence it in the direction of restoration of the state of Lithuania. This article seeks to show to what extent the Helsinki Final Act of CSCE signed in 1970s influenced the evolution of the Lithuanian freedom cause.
Keywords: Lithuanian occupation; emigree; Helsinki pact; Lithuanian liberation movement